Eukaryotic Initiation Factor 5A2 localizes to actively translating ribosomes to promote cancer cell protrusions and invasive capacity - Arantxa Martínez-Férriz; Carolina Gandía; José Miguel Pardo-Sánchez; Alihamze Fathinajafabadi; Alejandro Ferrando; Rosa Farràs (Cell Communication and Signaling, 2023)
Abstract Background Eukaryotic Initiation Factor 5A (eIF-5A), an essential translation factor, is post-translationally activated by the polyamine spermidine. Two human genes encode eIF-5A, being eIF5-A1 constitutively expressed whereas eIF5-A2 is frequently found overexpressed in human tumours. The contribution of both isoforms with regard to cellular proliferation and invasion in non-small cell lung cancer remains to be characterized. Methods We have evaluated the use of eIF-5A2 gene as prognosis marker in lung adenocarcinoma (LUAD) patients and validated in immunocompromised mice. We have used cell migration and cell proliferation assays in LUAD lines after silencing each eIF-5A isoform to monitor their contribution to both phenotypes. Cytoskeleton alterations were analysed in the same cells by rhodamine-phalloidin staining and fluorescence microscopy. Polysome profiles were used to monitor the effect of eIF-5A2 overexpression on translation. Western blotting was used to study the levels of eIF-5A2 client proteins involved in migration upon TGFB1 stimulation. Finally, we have co-localized eIF-5A2 with puromycin to visualize the subcellular pattern of actively translating ribosomes. Results We describe the differential functions of both eIF-5A isoforms, to show that eIF5-A2 properties on cell proliferation and migration are coincident with its features as a poor prognosis marker. Silencing of eIF-5A2 leads to more dramatic consequences of cellular proliferation and migration compared to eIF-5A1. Overexpression of eIF-5A2 leads to enhanced global translation. We also show that TGFβ signalling enhances the expression and activity of eIF-5A2 which promotes the translation of polyproline rich proteins involved in cytoskeleton and motility features as it is the case of Fibronectin, SNAI1, Ezrin and FHOD1. With the use of puromycin labelling we have co-localized active ribosomes with eIF-5A2 not only in cytosol but also in areas of cellular protrusion. We have shown the bulk invasive capacity of cells overexpressing eIF-5A2 in mice. Conclusions We propose the existence of a coordinated temporal and positional interaction between TFGB and eIF-5A2 pathways to promote cell migration in NSCLC. We suggest that the co-localization of actively translating ribosomes with hypusinated eIF-5A2 facilitates the translation of key proteins not only in the cytosol but also in areas of cellular protrusion. Video Abstract